Pengembangan Nilai Karakter Melalui Pendekatan Living Values Education di Kelas Tinggi Mi Al-Ma’arif 1 Kabupaten Sorong - Afroh Nailil Hikmah; Nasrul Fauzi; Naimah Nuraini (MISOOL: Jurnal Pendidikan Dasar, 2022)
This thesis discusses the Development of Character Values Through the Living Values Education Approach in MI AL-Ma'arif 1 High Class, Sorong Regency. The researcher focuses this research on: 1) School efforts in developing character values through the Living Values Education approach in high grades. 2) Character developed through the Living Values Education approach and its implementation by high grade students. This study uses the type of research Field Research, the subjects of this research are school principals, teachers of grades IV, V, and VI, as well as several students of grades IV, V, and VI. Data collection techniques using interviews, observation, and documentation.The results of this study are efforts to develop character values through the Living Values Education approach including the principal's policy, namely the Dhuha prayer habituation program, Friday infaq activities, memorizing short surahs before starting learning, and giving students the freedom to take part in competitions they are interested in. Furthermore, the teacher's efforts include: providing good examples during the learning process and social activities in schools, approaching students by looking at the background of each student, educating and developing character values with each appropriate technique, providing educational sanctions, and honing to always invite and direct students to always do good. Then the character values developed through the Living Values Education approach include: cooperation, humility, tolerance, peace, responsibility, unity and freedom